Perbandingan Kadar Glukosa Darah dengan Indeks Massa Tubuh di Kalangan Remaja Posyandu Kelurahan Jati Utomo - Artika, Cut Mutia; Fauziah, Ida; Sartini, Sartini; Rahmiati, Rahmiati (Jurnal Ilmiah Biologi UMA (JIBIOMA), 2024)
Blood glucose level represents the amount of sugar circulating in the bloodstream, originating from the breakdown of carbohydrates consumed in food and stored in the form of glycogen in the liver and skeletal muscles. Factors influencing blood glucose levels include dietary patterns, lifestyle, changes in body weight, age, and level of physical activity. Body Mass Index (BMI) is used to assess an individual's nutritional status by comparing their weight and height. This research was conducted to investigate the correlation between blood glucose levels and BMI among adolescents at the Adolescent Integrated Health Service Post in Jati Utomo Sub-District, Binjai City. Involving 30 adolescents, this study employed tests of normality and Spearman correlation analysis to analyze the data. The research findings indicate a strong correlation between BMI and blood glucose levels, with a correlation coefficient (r) of 0.67. This suggests that higher BMI correlates with higher blood glucose levels, providing valuable insights into the relationship between BMI and metabolic health in adolescents.